Linking leadership ethics and intergroup relationship through the revision of leadership theories and intergroup relationship - Mohd. Sohaimi Esa; Romzi Ationg; Siti Aidah Lokin; Sirahim Abdullah; Abang Mohd Razif Abang Muiz; Mohd. Azri Ibrahim (Solid State Technology, 2020)
This paper review and evaluates selected theories of leadership and intergroup relationship. It summarizes issues raised by the scholars pertaining to the theories. Accordingly, this paper argues that there is a theoretical relationship between ethical leadership and intergroup relations. This portrays that ethical leadership factor is of a key course that enable any organization to successfully achieve its common goals. For this reason, improving leadership ethics is vital for such aspiration. This, however, argued that a specific observation on intergroup relationship within the organization is needed. It is hoped that such move will result in not only attainment of organization goals, but also improve leader’s quality.rsity’s students into future-proof graduates.